Diagnostics of Electron Temperature in Laser Produced Plasma from Iron Using Plasma X-ray Emission - Awadalla, Mohamed Osman; Nour, A. H. (AENSI Publishing, 2016)
X-rays emitted from plasmas were used to calculate the temperature from the X-ray line intensity ratio. We used a Nd: YAG laser system, frequency doubled 532 nm, emitting 40 ps pulses at repetition rate 1 to 10 Hz. The energy on target was about 30 mJ corresponding to an intensity of 1013 Wcm2. X-ray spectra in the range 12 - 17 Å from iron targets were detected. According to Boltzmann law, a plot of the logarithmic term versus ΔE yields a straight line with slope equal to –1/T. The plasma electron temperature determined in this way was ~ 13.18 eV for Fe.